New compounds of Siolmatra brasiliensis and inhibition of in vitro protein glycation damage - dos Santos, Carlos Henrique Corrêa; Talpo, Tassiana Cristina [UNESP]; Motta, Bruno Pereira [UNESP]; Kaga, Anderson Kiyoshi [UNESP]; Baviera, Amanda Martins [UNESP]; Castro, Rosane Nora; da Silva, Virgínia Cláudia; de Sousa-Junior, Paulo Teixeira; Wessjohann, Ludger; de Carvalho, Mário Geraldo (Elsevier, 2019)
Twenty compounds were isolated from the hydroethanolic extract of the stems of Siolmatra brasiliensis, five flavonoids, two lignans, one glucosyl phytosterol, seven nor-cucurbitacins, one new phenolic derivative named siolmatrin (1) and four new dammarane-type saponins named siolmatrosides II-V (2–5), the structures of the compounds were assigned by means of 1D and 2D NMR experiments and HRESIMS of the natural compounds and some acetyl derivatives. The effects of the crude hydroethanolic extract (SbExt) and the ethyl acetate fraction (SbEtAc) of Siolmatra brasiliensis stems on the formation of advanced glycation end-products (AGEs) were also investigated. In the in vitro model system of protein glycation using bovine serum albumin (BSA) and glucose, addition of SbExt or SbEtAc inhibited the formation of fluorescent AGEs, in parallel to minor levels of fructosamine (SbEtAc) and markers of tyrosine and tryptophan oxidation (SbExt and SbEtAc). Protein crosslinking, which represents changes of late stages of protein glycation, was reduced in the presence of SbExt and SbEtAc. Siolmatra brasiliensis stems seem to be a promising source of compounds having ability to prevent glycoxidation changes, arising as an interesting option to be studied as a complementary therapy for complications of diabetes.
Keywords: Antiglycation activity; Cucurbitaceae; Diabetes melittus; Phenolic compounds; Siolmatra brasiliensis; Triterpenoids